Studi Lokasi Evakuasi Masyarakat dalam Mitigasi Banjir Lahar Dingin di Sisi Selatan Gunung Marapi - Wulandari, Fitri; Edial, Helfia; Purwaningsih, Endah (Lembaga Yasin AlSys, 2025)
This study aims to: 1) Map the cold lava flow zone on the south side of Mount Marapi. 2) Mapping the cold lava flood hazard zone on the south flank of Mount Marapi. 3) Mapping the location of community evacuation in mitigating cold lava flood on the south side of Mount Marapi. This type of research uses descriptive quantitative approach. Data collection techniques were literacy study, internet searching and field survey. Data processing analysis techniques using scoring and weighting methods. The data visualized in this research are 8 rivers upstream from the south side of Mount Marapi. The results of this research are: There are 3 results of this research: 1) Nagari located in the cold lava flood flow zone on the south side of Mount Marapi are Nagari in Tanah Datar Regency: Sungai Jambu, Parambahan, Limo Kaum, Simabur, Pariangan, Batu Basa, Padang Magek, Paninjauan, Panyalaian, Batipuh Ateh and Sumpur. Nagari in Padang Panjang City: Kota Panjang, Ngalau, Pasar Usang and Ganting. 2) There are 3 classes of cold lava flood hazard zones: low hazard 23.12%, medium hazard 46.44% and high hazard 30.44%. 3) 8 evacuation locations are obtained, namely in Nagari Batu Basa, Nagari Limo Kaum, Nagari Batipuah Ateh, Nagari Padang Panjang and Nagari Simabur.